ANALISIS PERBEDAAN PERLAKUAN ZAKAT DALAM PAJAK (STUDI KOMPARATIF INDONESIA DAN MALAYSIA) - Sayuti, Muhammad (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
Zakat and taxes are two very important things in the socio-economic life of society. Zakat is a form of worship that emphasizes the integration between divine aspects and the socio-economic life of society. However, the low awareness of muzaki to pay zakat is one of the reasons for the low national zakat fundraising. In the context of Indonesia and Malaysia, there are differences in the treatment of zakat in taxes. Therefore, this study will analyze differences in the treatment of zakat in taxes between Indonesia and Malaysia. This research uses a comparative study method between Indonesia and Malaysia in the treatment of zakat in tax to provide a clear picture of the differences in the treatment of zakat in tax in Indonesia and Malaysia. The results of the study state that the distribution of zakat in Indonesia and Malaysia, can be used as an income tax deduction with the requirement of a large amount through a recipient agency/institution authorized by the government. Government Regulation (PP) No. 60 of 2010 concerning Zakat or Religious Contributions of a Mandatory Nature that can be Deducted from Gross Income with good coordination between the zakat authority and the tax authority can increase the help of zakat payers (muzakki) and taxpayers so that it is expected that tax and zakat revenues will increase. Some differences in the treatment of zakat in tax in Indonesia there is a collection and distribution of zakat is governed by one body, while in Malaysia the body of collection and distribution of zakat in different responsibilities. The factors that influence the awareness of muzakki to pay zakat include knowledge about zakat, religious factors, social factors, economic factors, regulatory factors, zakat management factors, education factors, environmental factors, perception factors, compliance factors, and service factors. The government and zakat management institutions must pay attention to these factors to increase the awareness of muzakki to pay zakat and the collection of national zakat funds.